Personal & professional development for business students - Dowson, Paul (SAGE, 2015)
This book is unique in the areas of personal development, employability and responsibility in business. First, it brings all these areas together in a coherent and rigorous fashion. Second, it recognises what is needed for the Twenty-First Century business student in an environment, which demands both integrated thinking and integrity. Third, it is focused in practice, recognising the different functional areas and outlining what responsibility looks like in each of these. Fourth, it acts as a credible means of integrating the business curriculum by embedding personal development in each of the professional areas.